The expression regulation and clinical significance of miRNA in esophageal cancer - Ya-Nan LI; Li ZHANG; Zhi-Fan XIONG (Yixue xinzhi zazhi)
China is one of the countries with the high incidence of esophageal cancer in the world. Hence it is of great significance to explore the pathogenesis of esophageal cancer and screen out biomarkers for diagnosis and prognosis as well as therapeutic targets. As a novel biomarker, microRNA (miRNA) has been widely studied in esophageal cancer. In this paper, the expression regulation mechanism of miRNA in esophageal cancer and its role in clinical diagnosis, treatment and prognosis of esophageal cancer are reviewed.